Prognostic Factors for Excellent Response to Initial Therapy in Patients With Papillary Thyroid Cancer From a Prospective Multicenter Study - Dong, Wen-Wu; Zhang, Da-Lin; He, Liang; Shao, Liang; Wang, Zhi-Hong; Lv, Cheng-Zhou; Zhang, Ping; Huang, Tao; Zhang, Hao (Frontiers in Oncology, 2022)
Prognostic factors for excellent response (ER) to initial therapy in patients with papillary thyroid cancer (PTC) have not been determined. In this study we investigated the response to initial therapy in PTC patients and independent prognostic factors for ER in a prospective multicenter study in China. A total of 506 PTC patients from 9 centers in China were enrolled in this study, all of whom underwent total or near total thyroidectomy with lymph node dissection and subsequent radioiodine therapy. Univariate and multivariable logistic regression analyses were carried out to determine independent prognostic factors for ER. The optimal cut-off value of the number of metastatic lymph nodes for predicting ER was determined by receiver operating characteristic curve. A total of 139 patients (27.5%) achieved ER after initial therapy. Extrathyroidal extension, the number of metastatic lymph nodes, and preablative-stimulated thyroglobulin (Ps-Tg) were independent risk factors for ER for the entire population. In subgroup analysis, extrathyroidal extension and Ps-Tg were independent risk factors for ER in pathological N1a patients, while the number of metastatic lymph nodes and Ps-Tg were independent risk factors for ER in pathological N1b patients. The appropriate cut-off values of the number of metastatic lymph nodes in predicting ER were 5 and 13 for the entire population and pathological N1b PTC patients, respectively. PTC patients with more metastatic lymph nodes were more likely to fail to achieve ER. Extrathyroidal extension, the number of metastatic lymph nodes, and Ps-Tg were important prognostic factors for ER after initial therapy in PTC patients.